2019
DOI: 10.1142/s0218202520500050
|View full text |Cite
|
Sign up to set email alerts
|

Multilevel approximation of Gaussian random fields: Fast simulation

Abstract: We propose and analyze several multilevel algorithms for the fast simulation of possibly nonstationary Gaussian random fields (GRFs) indexed, for example, by the closure of a bounded domain [Formula: see text] or, more generally, by a compact metric space [Formula: see text] such as a compact [Formula: see text]-manifold [Formula: see text]. A colored GRF [Formula: see text], admissible for our algorithms, solves the stochastic fractional-order equation [Formula: see text] for some [Formula: see text], where [… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 52 publications
1
29
0
Order By: Relevance
“…Proposition 2 Let Z , Z be GRFs colored by T and T , respectively, see (20), with covariance functions denoted by and , cf. (29). Then,…”
Section: Corollary 1 Let Assumptionmentioning
confidence: 98%
See 2 more Smart Citations
“…Proposition 2 Let Z , Z be GRFs colored by T and T , respectively, see (20), with covariance functions denoted by and , cf. (29). Then,…”
Section: Corollary 1 Let Assumptionmentioning
confidence: 98%
“…We recall that the covariance function (29) In the next lemma, this relation and (19) are exploited to characterize continuity of the covariance function in terms of the color T of the GRF Z . Proposition 2 Let Z , Z be GRFs colored by T and T , respectively, see (20), with covariance functions denoted by and , cf.…”
Section: Corollary 1 Let Assumptionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, the computational benefits of the stochastic partial differential equation approach in the Gaussian case with differential operators as in equation 5 k ∈ N have already been emphasized by . Recent developments in numerical methods for fractional operators furthermore facilitate treating the whole admissible parameter range φ > 0 while maintaining low computational complexity Herrmann et al, 2020). Specifically, it is a well-known result that, in the non-fractional case D 1 = κ 2 − @ 2 =@t 2 , inverses of the symmetric, elliptic differential operator D 1 , when discretized by means of a finite element method with continuous piecewise linear basis functions on the mesh 0 = s 1 < : : : < s K = t max as used in equation 14, can be realized numerically with multilevel preconditioned iterative solvers in a complexity which is (essentially) linear in the number K of mesh nodes; see, for example Xu (1992).…”
Section: Kristin Kirchner (Delft University Of Technology)mentioning
confidence: 99%
“…Specifically, it is a well-known result that, in the non-fractional case D 1 = κ 2 − @ 2 =@t 2 , inverses of the symmetric, elliptic differential operator D 1 , when discretized by means of a finite element method with continuous piecewise linear basis functions on the mesh 0 = s 1 < : : : < s K = t max as used in equation 14, can be realized numerically with multilevel preconditioned iterative solvers in a complexity which is (essentially) linear in the number K of mesh nodes; see, for example Xu (1992). Recently, it has been shown that, given a prescribed accuracy, this complexity can also be achieved in the fractional case (Herrmann et al, 2020). The numerical inversion of the operator D 2 = κ + @=@t introduced in Section 3.2.1 and treated in a variational framework with a Petrov-Galerkin discretization in Appendix B, however, requires an additional discussion due to its asymmetry.…”
Section: Kristin Kirchner (Delft University Of Technology)mentioning
confidence: 99%